Chronicle of Central Bank policy - Saunders, Muriel (Central Bank of Barbados [Bridgetown]BB, 1998)
Includes all aspects of Central Bank activity in so far as they were intended to have an impact on the performance of the economy. Lists credit, interest rate, exchange rate, exchange control policies as well as activities by the Central Bank to make finance available to exporters, small business and other producers. Mentions also initiatives by the Central Bank in the offshore financial sector.